The Impact of Pediatric Basal Ganglia Stroke on Mental Health in Children: Report of 2 Cases - Badar, Sidrah A. (Child Neurol Open, 2020)
BACKGROUND: The impact of basal ganglia stroke on mental health is better described in adults than in children. We report 2 children with significant mental health issues after basal ganglia stroke. CASE REPORTS: Patient 1, an 8-year-old boy, had mild anxiety before his left basal ganglia stroke. Post-stroke, he developed severe anxiety, obsessions, depression, and attention deficit hyperactivity disorder, in addition to a right hemiplegia and some mild chorea. He gradually improved over 3 years with psychiatric care and medication but continued to have residual symptoms. Patient 2, a 10-year-old boy, had no history of mental health issues before his right basal ganglia stroke. Post-stroke, he developed significant anxiety and mild depression, along with a left hemiplegia. He improved over 9 months and returned to his mental health baseline. CONCLUSIONS: Mental health issues after basal ganglia stroke in children can be significant, and recovery can take months to years.